KESIAPAN PENGEMBANGAN EKONOMI DI PESANTREN AL ANWAR 3 SARANG, JAWA TENGAH - Habibussalam, Habibussalam (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2020)
The increasing level of middle class welfare in Indonesia is not only a gift for the country, but also for Muslims as the majority. Unfortunately, these economic improvements have not yet fully reached the pesantren environment widely, especially in Central Java Province. Seeing this condition, the provincial government cooperated with Bank Indonesia to provide pesantren economic development assistance programs. One of the participants is Al Anwar 3 Islamic Boarding School located in Sarang District, Rembang Regency. The launch of the pilot project is certainly the beginning of the empowerment of the santri group, which has not been explored to date. Applying a qualitative descriptive method, this research analyzes how the readiness of the pondok in developing the initial program, which later is expected to run continuously. Looking at the research results obtained, the Al Anwar 3 pesantren is quite ready to run the program, only in the future some strategic aspects, such as land preparation and increased synergy between internal parties of the cottage need to be improved so that the long-term policy objectives can be achieved.